Improving writing skills : memos, letters, reports and proposals - Berger, Arthur Asa, 1933- (Survival skills for scholars., 1993)
This brief, practical guide illustrates the most common kinds of business correspondence that a university professor is required to produce and offers useful advice to make these communications as effective as possible. The author also offers general suggestions on effective writing, including brainstorming and collaborating, persuasion, outlining and revising, and designing documents.